2007
DOI: 10.1002/jgm.1075
|View full text |Cite
|
Sign up to set email alerts
|

A dimethylmaleic acid–melittin‐polylysine conjugate with reduced toxicity, pH‐triggered endosomolytic activity and enhanced gene transfer potential

Abstract: Modification of the polycationic carrier PLL with DMMAn-masked melittin not only enhances gene transfer efficiency, but also strongly reduces the acute toxicity of melittin and PLL. Hence this modification might be useful for optimizing polycationic gene carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 35 publications
1
68
0
Order By: Relevance
“…Their sizes could not be measured at pH 5.5 and 6.0 (Figure 4a) due to aggregation. This was a result of the weakened solubility of N -nap- O -MalCS in the aqueous phase caused by acid hydrolysis of its maleoyl groups [80,81]. This phenomenon accelerated at 37°C compared to 25°C (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…Their sizes could not be measured at pH 5.5 and 6.0 (Figure 4a) due to aggregation. This was a result of the weakened solubility of N -nap- O -MalCS in the aqueous phase caused by acid hydrolysis of its maleoyl groups [80,81]. This phenomenon accelerated at 37°C compared to 25°C (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…7). [174,175] Endosomolysis can not only be achieved with toxins known from nature: some synthetic vectors display this feature as well. For example bPEI is not only used for the complexation of nucleotides, it is also known to have some inherent endosomolytic ability.…”
Section: Disulfides For the Attachment Of Endosomolytic Agentsmentioning
confidence: 99%
“…The simplest strategy to improve the transfection efficiency of PLys polyplexes is to provide them with endosome-escaping functions, avoiding lysosomal degradation of loading pDNA. Several previous studies have reported about the integration of endosome-escaping elements into PLys polyplexes, including membrane-fusion peptides [11,12] and buffering units with low pKa, such as histidine. [13,14] [15,16] .…”
Section: Introductionmentioning
confidence: 99%